La cátedra de Derecho Natural y de Gentes: Continuidad de la enseñanza de elementos del derecho español en la primera década de la Universidad de Buenos Aires (Temas de Historia Argentina y Americana, 2022)
The University of Buenos Aires, which emerged within the framework of the Rivadavian reforms, was the first university in the Río de la Plata independent of Spain. However, there was a marked continuity in its cloisters with respect to the viceroyalty period. Depending on the study area, this link could be greater. In the present work we intend to investigate the chair of Natural and People's Law, as it is a key area in the training of future lawyers and it is the subject taught by the first rector of the university. The investigation will allow us to see the importance of the contents taught there through the manual written by their teacher, which will facilitate the analysis of the relationship that their contents and didactics preserved with respect to the Spanish training of which their first teachers were inheritors.
Keywords: University of Buenos Aires; Natural and People's Law; Antonio Sáenz; Pedro José Agrelo